ANALISIS EFISIENSI PENGELOLAAN PIUTANG PADA PT. PELABUHAN INDONESIA III (PERSERO) CABANG TERMINAL PETIKEMAS SEMARANG - Adam - Zakiya; Yuli - Sudarso; Taviyastuti - Taviyastuti (Politeknik Negeri Semarang, 2016)
The aims of this study are to analyze theadministrative processes of making notes andanalyze each completed transaction ofadministrative procedures of receivables thatoccurred during the period of November 2014to April 2015 and provide recommendationsas an input to the company. The method usedis qualitative method with descriptivecharacteristic. This research used primaryand secondary data which were collected bydoing observation, interview techniques andarchives obtained from the company. Thedata consisted of 254 transactions processedwithin 181 days. The results show that theadministrative procedures implemented by thecompany are too long and not correspond tothe flow round of the ship in the company.Based on the TRV (Turn Round Vessel)Shipping Agent is 7 days while the provisionsof the company as a whole 15 days(consisting of 5 days of making notescompleted and 10 days repayment period).There is accumulation of two transactions inone ship service. Thus it is suggested to makecomplete notes within 1 day and repaymentfor 6 days with the help of the online joborder system. With such efficiency, thecompany can increase profits from 20,038,738.34 to 33,397,897.233 in oneperiod is six months.